Magnetically Controlled Assembly of Dielectric Microspheres toward Photonic Molecules. (2nd July 2021) - Yin, Baipeng; Wu, Wubin; Dai, Chenghu; Jia, Hao; Zhang, Chuang; Yao, Jiannian
Abstract: The construction of "photonic molecules" with controlled sizes and shapes is of particular interest for the integration of miniaturized devices into optoelectronic chips. Here, a general approach is reported that allows the assembly of colloidal microspheres into coupled microcavities with high yield and large scale, utilizing magnetostatic interactions between diamagnetic building blocks dispersed in a ferrofluid under an external field. By precisely designing the local field gradient around diamagnetic microspheres, "virtual templates" can be formed to produce various coupled photonic structures, including diatomic heterogeneous molecules and polyatomic chain molecules. The diatomic structures can modulate the optical resonance modes upon the coherent coupling between microsphere cavities and serve as single‐mode wavelength‐tunable microlasers. The chain photonic molecules, as coupled resonator optical waveguides, could modulate the light propagation and store photons up to tens of picoseconds. The magnetically controlled assembly method is demonstrated, which provides a promising way for the facile and efficient fabrication of coupled microstructures for fascinating photonic and optoelectronic applications. Abstract : In this study, a universal yet efficient technique of magnetically controlled self‐assembly is developed for the construction of photonic molecules based on polystyrene microspheres. These coupled optical microcavities show fascinating and robust functionalities in manipulating photons in the resonance modes both spectrally and temporally.